2020
DOI: 10.1111/mec.15396
|View full text |Cite
|
Sign up to set email alerts
|

Differential divergence in autosomes and sex chromosomes is associated with intra‐island diversification at a very small spatial scale in a songbird lineage

Abstract: Recently diverged taxa showing marked phenotypic and ecological diversity provide optimal systems to understand the genetic processes underlying speciation. We used genome‐wide markers to investigate the diversification of the Reunion grey white‐eye (Zosterops borbonicus) on the small volcanic island of Reunion (Mascarene archipelago), where this species complex exhibits four geographical forms that are parapatrically distributed across the island and differ strikingly in plumage colour. One form restricted to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 98 publications
4
24
0
Order By: Relevance
“…Our study joins a growing number of systems demonstrating speciation at small spatial scales on islands (Bourgeois et al, 2020; Gabrielli et al, 2020; Heaney et al, 2018; Kisel & Barraclough, 2010; Osborne et al, 2020; Savolainen et al, 2006). We propose that transient geographic barriers coupled with local adaption across environmental gradients can contribute to the accumulation of phenotypic and taxonomic diversity.…”
Section: Discussionsupporting
confidence: 69%
“…Our study joins a growing number of systems demonstrating speciation at small spatial scales on islands (Bourgeois et al, 2020; Gabrielli et al, 2020; Heaney et al, 2018; Kisel & Barraclough, 2010; Osborne et al, 2020; Savolainen et al, 2006). We propose that transient geographic barriers coupled with local adaption across environmental gradients can contribute to the accumulation of phenotypic and taxonomic diversity.…”
Section: Discussionsupporting
confidence: 69%
“…Reunion and Mauritius are 170 km apart; both islands emerged from the ocean floor at a depth of 4.5-5 km, and were, therefore, never connected to each other [66]. While we did not specifically estimate migration rates, our phylogenetic data and previous work [67] suggest that gene flow between Reunion and Mauritius grey white-eyes is absent or very low and, if any, has clearly not prevented population divergence (F ST estimate of 0.18) (electronic supplementary material, figure S10; see also [37,38]). Our results also indicate that geographical differentiation has not been followed by secondary colonizations between islands, highlighting the role of inter-island colonization in the global diversification of white-eyes [26] and, more generally, the build-up of species diversity on oceanic archipelagos [11,68].…”
Section: Discussionmentioning
confidence: 68%
“…Recent studies have shown that more variation exists among the different geographical forms of the Reunion grey white-eye than would be expected under drift for both morphological and plumage colour traits [34,42]. Thus, while geographical isolation may have promoted evolutionary divergence between all forms, sexual selection also appears to have played a major role in the establishment of reproductive isolation [37]. Range expansion followed by range splitting or dispersal across the elevational gradient that led to the formation of the highland form seems to have been key in promoting ecological diversification within the lineage, with divergent selection pressures causing at least adaptive divergence and possibly also contributing to reproductive isolation [37,42,78].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations